Réponses

2014-03-08T12:41:02+01:00
A= (5x+3)(2x-4)
= 10x^2 - 20x + 6x - 12
= 10x^2 - 14x -12

B= (4x-3)^2
=(4x-3)(4x-3)
=16x^2 - 12x - 12x +9
=16x^2 - 24x +9

C= (5x+7)(5x-7)
25x^2 - 35x + 35x - 49
25x^2 -49

D= (6+10x)^2
=(6+10x)(6+10x)
=36 + 60x + 60x + 100x^2
=100^2 + 120x + 36
2014-03-08T12:42:10+01:00
Salut :)

A = (5x+3)(2x-4)
A = 5x x 2x + 5x x (-4) + 3 x 2x + 3 x (-4)
A = 10x² - 20x + 6x - 12
A = 10x² - 14x - 12

B= (4x-3)²
B = (4x)² - 2 x 4x x (-3) + 3²
B = 16x² - 24x + 9

C = (5x+7)(5x-7)
C = (5x)² - 7²
C = 25x² - 49

D = (6+10x)²
D = 6² + 2 x 6 x 10x + (10x)²
D = 36 + 120x + 100x²

J'espère t'avoir aidé(e)! :)